Psychological problems caused by the coronavirus (Covid-19) pandemic among deaf and hard of hearing students based on some demographic variable - Bahkali, Alwalaa Ali Yahya; Bahkali, Huda Ibrahim Ali (Journal of Educational and Psychological Sciences, 2022)
The study aims to identify the psychological problems resulting from the Corona Virus (Covid 19) pandemic among deaf and hard of hearing students enrolled in special education institutes and programs in the Kingdom of Saudi Arabia, in light of some demographic variables. The study sample consisted of (17) deaf and hard of hearing male and female students. The two researchers used the descriptive approach to conduct their study, and used a questionnaire prepared by them as a tool for collecting field material.The study reached several results, the most important of which are: One of the most important psychological problems resulting from the Corona Virus (Covid 19) pandemic among students who are deaf and hard of hearing: The two researchers recommend the need to provide a quiet environment, free of noise, with some games, and the possibility of reading or listening to various means of entertainment for the deaf and mute in light of the Corona Virus (Covid 19) pandemic, as the research found that they suffer - to a large extent - from feeling stress, boredom and severe discomfort, and the need for periodic follow-up by the family or residents with patients, as patients need careful follow-up of their physical and psychological condition, because they are exposed to psychological problems related to the constant reluctance to do anything such as forgetting the number of rak’as during prayer, and the necessity of having a partner, friend or relative - almost always - with deaf and dumb patients during the Corona Virus (Covid 19) pandemic, as the research found that patients suffer from the lack of someone who understands them, and they always feel lonely, and they do not find someone to turn to when they need help, and the necessity of conducting various recreational sessions for deaf and dumb patients, as the results of the research indicated that they always feel hopeless and helpless, and sleep a lot to escape from society.
Keywords: psychological problems; deaf and hard of hearing students; Corona Virus (Covid 19) pandemic